Development of enzymatic endpoints in Hyalella curvispina as future biomarkers in evaluations with acute sediment bioassays - Colombetti, Patricia Laura (2023)
Anthropic activities such as industrial, agricultural and urban activity can be a source of pollution gradients being proposed as a cause of habitat fragmentation. The Conlara River located in the northeast of San Luis province suffers different environmental pressures along its course, from urban to agro-industrial areas. Ourprevious work has shown that the presence of environmental stressors in the watershed negatively affects native fish. In this context, the objective of this work was to develop enzymatic endpoints in Hyalella curvispina as future biomarkers in evaluations with acute sediment bioassays. Sampling was carried out infour sites along the basin from S1 (upstream) to S4 (downstream). Water and sediment samples were taken from each site to carry out the bioassays on the bioindicator H. curvispina. Sediment samples were transferred to the laboratory and subsequently used for acute sediment bioassays (96 h exposure). In the samples, heavy metals and physicochemical parameters were determined. Biochemical parameters such as catalase (CAT), cholinesterase (ChE) and lipid peroxidation (TBARS) were evaluated after 96h of exposure to the sediments. For enzymatic determinations, 500 mg of H. curvispira was taken and 500uL of phosphate buffer was added. Then, they were homogenized and centrifuged at 10000 rpm for 12 min. The supernatant was then extracted for enzymatic determinations. Kruskall Wallis no parametric test was used to detect differences among sites. The biomarkers showed no significant differences in ChE (p=0,20) and CAT (p=0,20) after acute exposure, while in TBARS (p=0,10) enzimatic activity showed a gradient from site 1 (minor contamination) towards site 4 (higher contamination), indicating a stressful situation at the impacted site. Although the results showed no significant differences, there was a trend, probably due to the low number of replicates, suggesting an increase in the number of replicates in future test. It should also be noted that the samples were within the protein calibration curve, without the need for prior dilution of the amphipod pool. It is important to mention that these results are the first in semi-arid regions. Finally, although it is necessary to deepen these methodologies applied to native species of semi-arid zones, we reinforce the use of biochemical biomarkers in their ability to provide an early warning system, at the organismal level, before changes occur at the level of ecological organization.